2018
DOI: 10.3390/inventions3010015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Effect of Size and Pitch of Hydrophobic Square Patterns on the Pool Boiling Heat Transfer Performance of Cylindrical Copper Surface

Abstract: Abstract:In this work, pool boiling heat transfer tests were conducted for investigating the effects of the size and pitch of the hydrophobic square patterns on a copper test piece with the following dimensions: 40 mm long, 25 mm outer diameter, and 18 mm inner diameter. The size of the square patterns and the pitch were varied with an increment of 0.5 mm from 1 mm to 3 mm and from 4.5 to 5.5 mm, respectively. Among the various square patterns of different size and pitch, the 2 mm size square pattern with 5 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Sujith Kumar et al [ 51 ] quantified the optimal size and pitch distance of hydrophobic islands created using polymethyl methacrylate resin and trichlorosilane as a hydrophobic agent. They designed square patterns on various cylindrical copper rods, with sizes varying from 1 mm to 3 mm and pitches from 4.5 mm to 5.5 mm, all in increments of 0.5 mm.…”
Section: Literature Results On the Effect Of Surface Wettability On P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sujith Kumar et al [ 51 ] quantified the optimal size and pitch distance of hydrophobic islands created using polymethyl methacrylate resin and trichlorosilane as a hydrophobic agent. They designed square patterns on various cylindrical copper rods, with sizes varying from 1 mm to 3 mm and pitches from 4.5 mm to 5.5 mm, all in increments of 0.5 mm.…”
Section: Literature Results On the Effect Of Surface Wettability On P...mentioning
confidence: 99%
“…The inter-distance between hydrophobic spots should be sufficient to keep the replenishing liquid reaching heating surfaces and prevent early-stage bubble coalescence. In previous studies, Sujith Kumar et al [ 51 ] recommended values of around 3.2 mm for a particular set of experimental boundary conditions; however, generalisation to other applications should be further investigated. The pitch distances, sizes and shapes of hydrophobic areas on hydrophilic base surfaces are important and must be accurately determined and used to drive the design of biphilic surfaces.…”
Section: Analysis and Discussion The Optimization Of Biphilic Surfacesmentioning
confidence: 99%
“…Recent studies showed that hydrophilic and hydrophobic surfaces have significant abilities for boiling heat transfer enhancements [124][125][126][127][128]. Modified surfaces with the ability to enhance HTC (Heat Transfer Coefficient) and CHF (Critical of Heat Flux) values show at least one of the following properties: (a) increase in the frequency of the bubbles, (b) increase in the nucleation sites, (c) reduction of bubble's contact area, (d) low onset superheat for nucleate boiling [129,130].…”
Section: Wettability: Hydrophobic and Hydrophilic Coatingsmentioning
confidence: 99%